Komedi sebagai Sarana Kritik Sosial dalam Kesusastraan Prancis Abad ke-17 dan 18 - Husen, Ida Sundari (UI Scholars Hub, 2003)
The aim of comedy as a work of drama is to entertanin and ciritcize by making fun of the human characters and flaws or helpless situation. Comedy also makes fun of people from the county side who imitate the ways the Parisians dress and talk in exaggerated way. The works of the well-known comedy writers like Moli re (1622-1673), Marivaux (1688-1763) and Beaumarchais (1732-1799) deal with universal characters and problems, stereotypical human flaws, for example, stinginess, hypocrisy, arrogance, and snobbism.